A systematic review to assess the evidence-based effectiveness, content, and success factors of behavior change interventions for enhancing pro-environmental behavior in individuals - Rau, Henriette; Nicolai, Susanne; Stoll-Kleemann, Susanne (Frontiers in Psychology, 2022)
To reduce global greenhouse gas emissions in order to limit global warming to 1.5°C, individuals and households play a key role. Behavior change interventions to promote pro-environmental behavior in individuals are needed to reduce emissions globally. This systematic literature review aims to assess the a) evidence-based effectiveness of such interventions and b) the content of very successful interventions without limiting the results to specific emitting sectors or countries. Based on the “PICOS” mnemonic and PRISMA statement, a search strategy was developed, and eligibility criteria were defined. Three databases (Embase, PsycInfo, and Web of Science) were searched to retrieve and review potential literature. As a result, 54 publications from 2010 to 2021 were included in the analysis. The results show that most interventions only have small positive effects or none at all. A total of 15 very successful interventions focused on the sectors of mobility, energy, and waste and incorporated improved (infra-) structures, education, feedback, enablement or made the sustainable option the default. Six evidence-based recommendations for content, timing, and setting are deducted and given for interventions on enhancing pro-environmental behavior (PEB). In summary, although the various interventions and intervention types to promote PEB differ in their effectiveness, very successful interventions have common elements. Future research should focus on high-/low-impact and high-/low-cost behavior to develop interventions that aim at high-impact but low-cost behavior changes, or avoid low-impact but high-cost behavior.